The Impact of the Artistic Dimension on the Identity of the Urban Townscape (Al-Kindi Street as a Case Study) - Sudad Saeb Ibrahim; Ammar Saleh Ashour (Journal of Engineering)
The artistic dimension appears as an important factor in urban townscape's identity shaping, as many cities in the world have a different identity through the different artistic elements in it, the artistic dimension is meant within the research (set of artistic elements that can contribute to urban identity shaping, whether on architecture or on urban design in addition to public, urban arts). Many previous global studies have dealt with one type or more of art affecting the urban townscape identity of specific cities as a case study. Thus, we can diagnose the research problem as (the lack of local knowledge about the role of the artistic dimension in all its components in achieving the urban townscape identity), and the research assumes that (the artistic dimension has an important and clear impact on shaping and achieving the identity of the urban townscape, as is the case in the artistic dimension represented by advertising art in Al-Kindi Street), so the research aims to (Clarifying and highlighting the importance of the artistic dimension in achieving the identity of the urban scene and its role in the mental image and memory of society). Al-Kindi Street in Baghdad is a local case study to clarify the impact of the artistic dimension represented by advertising art, the research concluded that advertising art has a clear and strong impact on the urban townscape and achieving its clear identity, and the research recommends paying attention to the arts to improve the urban townscape in Baghdad.